2024
DOI: 10.3390/antiox13040390
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Supplementation with Silymarin on Cardiovascular Risk Factors: A Systematic Review and Dose–Response Meta-Analysis

Shooka Mohammadi,
Omid Asbaghi,
Reza Afrisham
et al.

Abstract: It has been suggested that silymarin (SIL) supplementation has positive effects on cardiovascular health and reduces the risk of cardiometabolic syndrome (CMS). This systematic review and dose–response meta-analysis assessed the impacts of SIL administration on cardiovascular risk factors. A systematic search of multiple databases was performed to identify eligible controlled trials published up to January 2023. The analysis used a random-effects model and included 33 trials with 1943 participants. It was reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
(252 reference statements)
0
2
0
Order By: Relevance
“…Fatigue was evaluated as mild, moderate, or severe depending on VAS scores (< 20, 20-50, and >50, respectively) [31,32]. Depression was assessed depending on BDI-II score as follows: no depression (0-13), mild to moderate depression (14)(15)(16)(17)(18)(19), moderate to severe depression (20)(21)(22)(23)(24)(25)(26)(27)(28), and severe depression (29-63) [28]. Anxiety level was indicated by GAD-7 score: minimal, mild, moderate, and severe anxiety for GAD-7 scores of 0-4, 5-9, 10-14, and 15-21, respectively [29].…”
Section: Fatigue Depression and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue was evaluated as mild, moderate, or severe depending on VAS scores (< 20, 20-50, and >50, respectively) [31,32]. Depression was assessed depending on BDI-II score as follows: no depression (0-13), mild to moderate depression (14)(15)(16)(17)(18)(19), moderate to severe depression (20)(21)(22)(23)(24)(25)(26)(27)(28), and severe depression (29-63) [28]. Anxiety level was indicated by GAD-7 score: minimal, mild, moderate, and severe anxiety for GAD-7 scores of 0-4, 5-9, 10-14, and 15-21, respectively [29].…”
Section: Fatigue Depression and Anxietymentioning
confidence: 99%
“…Its main indications are viral- and toxin-induced hepatitis, alcoholic and non-alcoholic fatty liver disease, cirrhosis, Amanita mushroom poisoning, and hypercholesterolemia [ 10 , 11 , 12 ]. In addition, recent clinical studies have reported the efficacy of silymarin and/or silibinin in diabetes [ 13 ], cardiometabolic syndrome [ 14 ], Alzheimer’s disease [ 15 ], melasma [ 16 , 17 ], and as radioprotective agents [ 18 ]. Silymarin has a good safety profile, and no significant toxicity has been reported in human studies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%